Opportunities for promoting gender equality in rural Ethiopia through the commercialization of agriculture - Aregu, Lemlem; Bishop-Sambrook, C.; Puskur, Ranjitha; Tesema, E. (International Livestock Research Institute, 2010)
Rural women in Ethiopia represent a tremendous productive resource in the agricultural sector. They are major contributors to the agricultural workforce, either as family members or in their own right as women heading households. However, despite recent policy initiatives to strengthen the position of women in the agricultural sector, a mixture of economic constraints, cultural norms and practices continue to limit their contribution to household food security and, to a lesser extent, inhibits the commercialization of the sector. Gender roles and relationships influence the division of work, the use of resources, and the sharing of the benefits of production between women and men. In particular, the introduction of new technologies and practices, underpinned by improved service provision, often disregards the gendered-consequences of market-oriented growth and many benefits bypass women. Not only do these circumstances have implications for issues of equality but also may be detrimental to the long-term sustainability of development initiatives. Despite the crucial role of the agricultural sector in the Ethiopian economy, studies on gender aspects of agricultural commercialization are relatively scarce. The main purpose of this paper is to contribute to the knowledge base about implications of gender roles and responsibilities for the development of the agricultural sector. This paper discusses gender issues in the context of the Improving Productivity and Market Success (IPMS) of Ethiopian Farmers’ Project being implemented by the International Livestock Research Institute (ILRI) and the Ethiopian Ministry of Agriculture and Rural Development. The findings are based on qualitative studies undertaken by the IPMS gender research team and Research and Development Officers in 10 pilot learning woredas (PLWs) located in 4 regions of the country. The study had three objectives: to increase the understanding of the different roles of women and men in agricultural activities, marketing and decision making, and their share in the benefits; to identify potential barriers for women’s and men’s participation in market-led development initiatives and technology adoption; and to identify what actions may overcome some of these barriers.